MODERN CONDITION AND PROSPECTS OF DEVELOPMENT OF TRANSPORT SUPPORT DURING WHEAT HARVESTING (Transport systems and technologies, 2018)
The paper analyses the current state and prospects of development of transport sup-port for wheat harvesting. The data on availability of combine harvesters in Ukraine are presented; their loads are segmented in the context of regions and countries specializing in wheat cultivation. The modern problems of organization and planning of transport support during wheat harvesting are researched. It has been established that an im-portant reserve for improving efficiency of agricultural enterprises is improvement of machinery use. Under conditions of insufficient renewal and limitation of the amount of technical equipment, careful organization and planning of the need for wheat harvesting vehicles come into the foreground. Sufficient attention should be given to operations management and control over the process of crop transportation at every agricultural enterprise specialising in wheat harvesting.
Keywords: transport support, motor vehicles, combine harvesters, harvest, wheat.